INFLUENCE OF AN AGROTECHNOLOGY OF CULTIVATION OF A CARTHAMUS TINCTORIUS ON WATER CONSUMPTION AND ITS EFFICIENCY IN THE CONDITIONS OF THE SOUTH OF UKRAINE - Філіпов, Є. Г. (Scientific Progress & Innovations, 2014)
In the article the results of researches of influencing of agrotechnical receptions are resulted on productivity of plants of the Carthamus tinctorius, tilled in the conditions of irrigation of the South Ukraine. It is set on results researches, that at growing of the Carthamus tinctorius on the irrigated lands of southern Ukraine for achievement of productivity level of seeds of culture within the limits of 2.0-2.5 t/ha it is necessary to conduct ploughing on a depth 20-22 cm, to use space between rows 30 cm, to conduct sowing in early terms (ІІІ ten-day period the March) and bring in the mineral fertilizers by the dose N60P60. The terms of sowing and fertilizer have most particle of influence on forming of productivity of seeds.